Give the reason for the step taken from a proof.

<1 and <2 are a linear pair given
m<1 + m<2 = 180* ?

a. congruent supplements theorem
b. vertical angles theorem
c. linear pair postulate
d. congruent complements theorem

when i put < i hope you know what i mean and when i put an asterisk sign just replace it with a degrees sign in your mind.

  1. 👍
  2. 👎
  3. 👁

Respond to this Question

First Name

Your Response

Similar Questions

  1. math

    Consider the sequence of steps to solve the equation: 5(x - 3) = 7x 2 Step 1 ⇒ 10(x - 3) = 7x Step 2 ⇒ 10x - 30 = 7x Step 3 ⇒ 3x - 30 = 0 Step 4 ⇒ 3x = 30 Step 5 ⇒ x = 10 Identify the property of equality which yields

  2. Math

    Given: Triangle SVX is congruent to triangle UTX and Line SV is parallel to line TU. Prove: VUTS is a parallelogram. Statement : Reason. 1. Tri SVX is congruent to Tri UTX. Reason: Given. 2. Line SV is parallel to line TU. Reason:

  3. Math Calculus

    This is all about the intermediate value theorme.. You wish to visit you sweetheart, but you don't want to go all the way over to their house if your sweetheart isn't home. What sort of "existence proof" could you do beforehand to

  4. math

    give the reason to justify each step a. 4c+3(2+c)=4c+6+3c b. =4c+3c+6 c. =(4c+3c)+6 d. =(4+3)c+6 e =7c+6

  1. math

    Consider the sequence of steps to solve the equation: 2(x − 4) + 6x = 9x − 10 Which step in solving this equation is justified by the Commutative Property of Addition? Given ⇒ 2(x − 4) + 6x = 9x − 10 Step 1 ⇒ 2x − 8

  2. Mathematical induction. I'm stuck. So far I have..

    For all integers n ≥ 1, prove the following statement using mathematical induction. 1+2^1 +2^2 +...+2^n = 2^(n+1) −1 Here's what I have so far 1. Prove the base step let n=1 2^1=2^(1+1)-1 False. Someone else suggested that the


    When solving the equation, what property was used to go from step 3 to step 4? Step 1: -(2x+3= x-18 Step 2: -2x-3=x-18 Step 3: -3=3x-18 Step 4: 15=3x A)APOE B)SPOE C)MPOE D)DPOE

  4. geometry

    1)given-AB=CD,CD=EF prove-AB-EF (in 5 steps that show why it is corect; i.e two-column proof) 2)Given-

  1. Algebra 2

    Read the following proof of the polynomial identity a3+b3=(a+b)3−3ab(a+b). Step 1: a3+b3=a3+3a2b+3ab2+b3−3ab(a+b) Step 2: a3+b3=a3+3a2b+3ab2+b3−3a2b−3ab2 Step 3: a3+b3=a3+3a2b−3a2b+3ab2−3ab2+b3 Step 4: a3+b3=a3+b3

  2. Algebra 2

    This problem has four parts, Part A, Part B, Part C, and Part D. Read the proof, and then answer all four parts. Given: (a−b)2 Prove: (a−b)2=a2−2ab+b2 Statements Reasons 1. (a−b)2 Given 2. (a−b)(a−b) Rewrite a power as

  3. Rate determining step

    I don't understand how to get a rate determining step. I have an energy diagram for a two-step conversion where the first step Ea is about 18 units. The energy then goes down about 4 units and rises again about 10 units to the

  4. Algebra

    Josephine solved a quadratic equation: (x+6)^2=49. Her work is shown below. Step 1: √(x+6)^2 = √49 Step 2: x+6 = 7 Step 3: x = 7−6 Step 4: x = 1 In which step did Josephine make an error? A- step 4 B- step 1 C- step 2 D-

You can view more similar questions or ask a new question.